Aliwalas improving passive environmental comfort in low-rise residential buildings using performance sketching - Estacio, Renee Aurora Ysobel W.; Del Castillo, Nicolo Precioso C. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Designing for passive environmental comfort is a key strategy in creating autonomous buildings that can withstand energy precarity in the current climate crisis. However, the assessment of building comfort performance is often neglected during the design stage, which is when decisions have the most impact on passive design. Similar to how an architectural sketch is a preliminary representation of the spatial program in the schematic design phase, a performance sketch is a rough model that can predict how the building might perform. This research project delves into the use of performance sketching as a tool to guide passive strategic decisions, with the aim of enhancing environmental comfort in the design of low-rise residential buildings in east Escopa IV.

Aliwalas was identified as a local concept of ideal comfort. Environmental comfort goals and metrics to support this concept, which can be assessed through performance sketching, were identified and incorporated into a structured passive design methodology. Performance sketching to meet the target metrics was then applied to design low-rise residential buildings in Escopa IV. The project showed that with the current accessible open-source simulation tools, performance sketching for general design projects can be practical at the building group and building design scales. The methods, tools, and metrics identified in this project can be applied to increase environmental comfort in Philippine architecture projects.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Dwellings -- Heating and ventilation; Buildings -- Environmental aspects; Architecture -- Human factors